Evidence of cloud and rainfall modification in a mid-sized urban area – A climatological analysis of Augusta, Georgia - Jordan McLeod; Marshall Shepherd; Max Appelbaum (City and Environment Interactions, 2024)
Cloud and rainfall distributions in urban spaces have implications for planning, hydrological response, reservoir management, renewable energy generation, transportation, and agricultural productivity. Studies have confirmed that large urban areas can initiate or modify precipitation, but there are still questions about the role of city size and atmospheric interactions. The majority of case study approaches have focused on large cities or urban clusters and have largely ignored small to moderate sized cities. Herein, an analysis of the Augusta, Georgia metropolitan statistical area is conducted. Using a gridded, daily multi-sensor precipitation dataset and satellite-based cloud cover climatology, the warm seasons (June, July, and August) covering the period from 2002 to 2019 were analyzed using spatial comparisons within an upwind-downwind framework and z-score statistics. Such methodologies have been published for larger urban areas. We confirmed that a moderate-sized city like Augusta, Georgia and neighboring Aiken, South Carolina is associated with spatial patterns consistent with the “urban rainfall effect” (URE) and possibly an “urban cloud effect” (UCE). Contextual analysis of other local mesoscale signatures related to nearby water bodies are also provided as a sanity check on process identification.